2021
DOI: 10.1038/s41598-021-88864-7
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of randomized clinical trials on the impact of oral vitamin C supplementation on first-year outcomes in orthopedic patients

Abstract: This meta-analysis aimed at investigating the impact of oral vitamin C supplementation on the post-procedural recovery of orthopedic patients, including functional outcomes and complex regional pain syndrome type I (CRPS I). Literature search using the Medline, Cochrane Library, and Embase databases from inception till March 2021 identified seven eligible randomized controlled trials with 1,361 participants. Forest plot revealed no significant difference in the functional outcomes at 6–12 months [standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In our study, depressive personality disorder was also considered a risk factor for CRPS I in radial head fracture patients. Hung et al [ 34 ] reported that psychiatric comorbidities (anxiety, depression, etc.) were present in 29% of CRPS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, depressive personality disorder was also considered a risk factor for CRPS I in radial head fracture patients. Hung et al [ 34 ] reported that psychiatric comorbidities (anxiety, depression, etc.) were present in 29% of CRPS patients.…”
Section: Discussionmentioning
confidence: 99%
“…For a specific outcome described in 10 or more studies, the possibility of publication bias was evaluated through visual inspection of a funnel plot. Potential impact from the result of an individual trial on the overall finding was evaluated with sensitivity analysis (i.e., leave-one-out approach) 24 , 25 . Two-tailed tests were conducted on all comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Between-study heterogeneity was assessed with I 2 statistics, while publication bias was evaluated with funnel plots and Egger’s test. The effect of the outcome of each study on the overall results was determined by sensitivity analysis (Hung et al, 2021). Subgroup analyses based on sibling-matched data, the duration of LEA exposure (i.e.…”
Section: Methodsmentioning
confidence: 99%